Descartes "onda demon" och kristen livskonst - Lennartsson,Julia (2025)
René Descartes’ Meditations on First Philosophy explores foundational philosophical and theological questions through a method of radical skepticism. Central to this exploration is the concept of the evil demon, a hypothetical being that challenges human capacity to comprehend and perceive reality. Descartes’ meditations are pivotal to the development of rationalist philosophy, bridging epistemological inquiry with theological reflection. This essay examines the theological implications of Cartesian skepticism through a content-based idea analysis, drawing on John Cottingham’s translation of the Meditations. Key theoretical frameworks include Pierre Hadot’s philosophy as a "way of life" and Zbigniew Janowski’s exploration of theodicy. The essay demonstrates the interconnectedness of philosophical and theological themes in Descartes’ work, with the evil demon and God as central elements. The demon functions not only as a metaphysical hypothesis or a symbol for confronting skepticism but also as a conceptual tool in contemporary epistemology, emphasizing the dualistic tension in Cartesian thought. Scholars such as Richard Foley and Roberta Imlay argue that the demon extends beyond a mere philosophical construct, offering a pragmatic framework for engaging with and sustaining Cartesian skepticism. The analysis situates Descartes’ philosophy as both a response to existential and epistemological dilemmas and as a model for addressing broader societal challenges. Foley and Imlay’s interpretations, grounded in Western philosophy, fail to resonate with other traditions, including Eastern spiritual frameworks. This gap opens avenues for future research, particularly in exploring intersections between Cartesian meditation and practices like Zen Buddhism, where consciousness and self-awareness are central themes.
Keywords: cartesiansk skepticism; den onda demonen; epistemologi; teologi; meditation; kristen filosofi; teodicé; förnuft; tro; sanning.